On some leap indices of Polycyclic Aromatic Hydrocarbons (PAHs). (17th August 2020) - Asif, Fatima; Zahid, Zohaib; Cancan, Murat
Abstract: Graph invariants are numerical values assigned to some molecular graph GM to characterize its topological properties. The second neighbourhood or a 2 –distance degree of any vertex v in a graph GM is the cardinality of its second neighbors. In this research article, we formulated some expressions for the leap Zagreb indices, leap hyper-indices and F – leap indices, depending on the second degree of a vertex, of a family of a molecular graph called Polycyclic Aromatic Hydrocarbons PAH s .